Green finance: From wishful thinking to marginal impact - Jan Pieter Krahnen; Jörg Rocholl; Marcel Thum (EconPol Forum, 2023)
The difficulty of establishing clear links between the origin of funds and their use calls into question the usefulness of ESG-oriented financing. Active investors may exert a formative influence on a company's environmental and social actions, not least by accepting a personal reduction in earnings. Passive investors will only be able to exert an influence if there are a large number of green investors and if markets are characterized by frictions and inefficiencies. In the case of the state, there is no comparable way for investors to exert an influence, as budget planning remains the preserve of the legislature. Combining private efforts towards green finance with public policies may render the former ineffective in achieving ESG goals.
Keywords: 330